The impact of sMICA/sMICB on immunochemotherapy outcomes in newly diagnosed diffuse large B-cell lymphoma - Yoon, Sang Eun; Park, Sujin; Cho, Junhun; Ryu, Kyung Ju; Yandava, Booma; Lee, Sewon; Kim, Seok Jin; Kim, Won Seog (Frontiers in Oncology, 2023)
Soluble MHC class I-related chain A (sMICA) and B (sMICB) play a critical role in tumor evolution and poor prognosis through an immune evasion mechanism. Thus, this study determines the interaction between sMICA/sMICB and the tumor immune environment in newly diagnosed diffuse large B-cell lymphoma (ND-DLBCL). Of the 262 patients, 47.3% (n = 124) presented stage III or IV at diagnosis and 50.8% (n = 133) had a high International Prognostic Index (IPI ≥ 3). The patients with high (p = 0.034 and 0.004), elevated lactate dehydrogenase (p = 0.002 and 0.030), advanced stage (p = 0.003 and 0.012), and higher IPI risk (p = 0.009, and 0.032) correlated with the detection of sMICA or sMICB. The median progression-free survival (PFS) of patients with sMICA (p = 0.006) or sMICB (p = 0.032) was inferior. Among the patients with advanced-stage or high IPI, those with sMICA or sMICB presented an inferior PFS and OS compared to those without. TNF-α, a pro-inflammatory cytokine, showed statistical significance with detected sMICA (p = 0.035) or sMICB (p = 0.044).Among anti-inflammatory cytokines, IL-1RA (P-value = 0.013) and IL-10 (p = 0.005) were associated with detecting sMICB, but not sMICA. In tissue samples, sMICA or sMICB detection did not correlate with the CD68/CD163 ratio. Conclusively, the identification of sMICA/sMICB presented unfavorable immunochemotherapy outcomes, and it was assumed that sMICA or sMICB and various cytokines interact, but the relationship with macrophage differentiation is unclear. Therefore, further research is needed to determine the relationship between sMICA/sMICB and tumor microenvironment in DLBCL.